An assessment of the impact of business incubation ecosystem to firm's performance in MTDC Technology Centre / Mohd Izwan Yusof, Mohd Khairul Hazwan Mohd Razali & Muhammad Nur Syafiq Abd Kadir. - Yusof, Mohd Izwan; Mohd Razali, Mohd Khairul Hazwan; Abd Kadir, Muhammad Nur Syafiq (2019)
There has been an increased interest in business incubation programs due to the rapid growth of the business incubators in developed and developing countries. Likewise, Malaysia has put forth the importance of entrepreneurship as the key driver to the national economic development to achieve the Malaysia Vision 2020. In conjunction with this, MTDC was established to promote business incubation program as one of their primary program to realise Malaysia's vision. Therefore, five business incubators initiated in the Universities and Research Institution within Johor and Selangor states. However, there has been a lack of study towards the performance of a business incubation program under the initiatives of the MTDC since its establishment. Thus, this study aimed to understand the performance of the business incubation program. A conceptual framework of the measurement for the firm's performance of the business incubation program was built and had identified five key indicators as the measurement indicators. A quantitative method was used in this study using a structured questionnaire instrument distributed to respondents. The results show a significant positive relationship between incubator ecosystems (infrastructure and facilities, business advisory and support, networking and connectivity, financial support services) and the firm's performance. An implication for business incubation program is the systematic measurement indicators for MTDC to assist in their future decisions on the service improvement, continuation or modification for their incubator services and ecosystems.